2018
DOI: 10.1037/xlm0000470
|View full text |Cite
|
Sign up to set email alerts
|

An imagery-induced reversal of intertrial priming in visual search.

Abstract: Maljkovic and Nakayama (1994) found that pop-out search performance is more efficient when a singleton target feature repeats rather than switches from 1 trial to the next-an effect known as priming of pop-out (PoP). They also reported findings indicating that the PoP effect is strongly automatic, as it was unaffected by knowledge of the upcoming target color. In the present study, we examined the impact of visual imagery on the PoP effect. Participants were instructed to imagine a target color that was opposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 51 publications
3
26
2
Order By: Relevance
“…In some ways, this finding fits with the literature, and in other ways not. Prior studies have shown that verbal representations sometimes have only a modest influence on visual search performance (Cochrane, Nwabuike, Thomson, & Milliken, 2018a;Theeuwes, Reimann, & Mortier, 2006). On the other hand, there are also theoretical accounts that posit semantic information is represented in the same brain networks that represent perceptual information (Amsel, Urbach, & Kutas, 2014;Barsalou, 2008;Tomasello et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some ways, this finding fits with the literature, and in other ways not. Prior studies have shown that verbal representations sometimes have only a modest influence on visual search performance (Cochrane, Nwabuike, Thomson, & Milliken, 2018a;Theeuwes, Reimann, & Mortier, 2006). On the other hand, there are also theoretical accounts that posit semantic information is represented in the same brain networks that represent perceptual information (Amsel, Urbach, & Kutas, 2014;Barsalou, 2008;Tomasello et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…If vision and visual imagery have common underlying representations (Ishai et al, 1999;Kosslyn, Thompson, & Ganis, 2006;O'Craven & Kanwisher, 2000), then it seems possible that event file binding could occur for representations that support visual imagery. In line with this idea, several recent studies have shown that visual imagery can influence visual search (Cochrane, Nwabuike, Thomson, & Milliken, 2018a;Cochrane, Zhu, & Milliken, 2018b;Reinhart, McClenahan & Woodman, 2015), binocular rivalry (Chang, Lewis, & Pearson, 2013), and visual identification (Wantz, Borst, Mast, & Lobmaier, 2015; though see Cochrane, Siddhpuria, & Milliken, 2018c). Together, the theory of event encoding and the empirical work cited above constitute a solid basis for examining whether representations that support visual imagery can contribute to event file binding.…”
Section: Introductionmentioning
confidence: 90%
“…Given the potential shortfalls in Maljkovic and Nakayama (1994) and the recent contradictory findings (Cochrane, Nwabuike, et al, 2018;Shurygina et al, 2019), we reexamined the conclusion that conscious expectancy does not influence the PoP effect by replicating the original study. Specifically, the two experiments of the present study evaluated whether the knowledge of the probability of a color change and vocalizing the upcoming target color produced the same results as those reported by Maljkovic and Nakayama's second and fourth experiments, respectively.…”
Section: Introductionmentioning
confidence: 90%
“…Recent findings cast further doubt on the conclusions of Maljkovic and Nakayama (1994). One such study investigated whether color imagery could override the PoP effect (Cochrane, Nwabuike, Thomson, & Milliken, 2018; see also Cochrane, Zhu, & Milliken, 2018). Participants performed a color singleton search task similar to that described previously.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to attentional performance, VWM is influenced by recent experiential history (Carlisle & Kristjánsson, 2018 ; Cochrane, Nwabuike, Thomson, & Milliken, 2018 ; Cunningham & Egeth, 2016 ; Kristjánsson, Saevarsson, & Driver, 2013 ). For example, Carlisle and Kristjánsson et al ( 2018 ) showed how priming and WM can affect one another and argued that implicit short-term memory and explicit VWM interact when they provide conflicting attentional instructions.…”
Section: The Recent Past Supports Attention and Working Memorymentioning
confidence: 99%